Transgenerational inheritance of centromere identity requires the CENP-A N-terminal tail in the C. elegans maternal germ line. - Reinier F Prosée; Joanna M Wenda; Isa Özdemir; Caroline Gabus; Kamila Delaney; Francoise Schwager; Monica Gotta; Florian A Steiner (PLoS Biology)
Centromere protein A (CENP-A) is a histone H3 variant that defines centromeric chromatin and is essential for centromere function. In most eukaryotes, CENP-A-containing chromatin is epigenetically maintained, and centromere identity is inherited from one cell cycle to the next. In the germ line of the holocentric nematode Caenorhabditis elegans, this inheritance cycle is disrupted. CENP-A is removed at the mitosis-to-meiosis transition and is reestablished on chromatin during diplotene of meiosis I. Here, we show that the N-terminal tail of CENP-A is required for the de novo establishment of centromeres, but then its presence becomes dispensable for centromere maintenance during development. Worms homozygous for a CENP-A tail deletion maintain functional centromeres during development but give rise to inviable offspring because they fail to reestablish centromeres in the maternal germ line. We identify the N-terminal tail of CENP-A as a critical domain for the interaction with the conserved kinetochore protein KNL-2 and argue that this interaction plays an important role in setting centromere identity in the germ line. We conclude that centromere establishment and maintenance are functionally distinct in C. elegans.